HYPERURICEMIA IN PREGNANT WOMEN WITH OBESITY - Tarasenko, K.V. (World of Medicine and Biology, 2013)
A tendency to increases in uric acid in blood serum was found in pregnant women with obesity (45 women) compared to a group of pregnant women with normal body mass (28 women). Hyperuricemia in pregnant women with obesity correlates positively with hyperinsulinemia and a marker of systemic inflammation – high sensitivity C-reactive protein.